2023
DOI: 10.1002/jid.3826
|View full text |Cite
|
Sign up to set email alerts
|

Social capital effects on resilience to food insecurity: Evidence from Kyrgyzstan

Bekhzod Egamberdiev

Abstract: This paper investigates the role of social capital in terms of trust and group membership in building household resilience to food insecurity. Using detailed ‘Life in Kyrgyzstan’ multi‐topic panel data, the research estimates resilience to food insecurity through the Resilience Index Measurement and Analysis (RIMA) approach, including different pillars and a resilience capacity index. The impact of social capital on resilience pillars and capacity is estimated using IV models for multiple endogenous variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…These factors are also known to have an impact on household food security. For instance, research has shown that social capital, economic capital, nutritional literacy, education, and demographic factors can influence the food security of households (Salarkia et al, 2013;Dastagiri et al, 2015;Ramesh et al, 2017;Egamberdiev, 2024).…”
Section: Research Backgroundmentioning
confidence: 99%
“…These factors are also known to have an impact on household food security. For instance, research has shown that social capital, economic capital, nutritional literacy, education, and demographic factors can influence the food security of households (Salarkia et al, 2013;Dastagiri et al, 2015;Ramesh et al, 2017;Egamberdiev, 2024).…”
Section: Research Backgroundmentioning
confidence: 99%